2005
DOI: 10.1086/444390
|View full text |Cite
|
Sign up to set email alerts
|

Serological Analysis of Serum Samples from Humans Exposed to Avian H7 Influenza Viruses in Italy between 1999 and 2003

Abstract: We evaluated the potential for avian-to-human transmission of low pathogenic avian influenza (LPAI) and highly pathogenic avian influenza (HPAI) H7N1 and LPAI H7N3 viruses that were responsible for several outbreaks of influenza in poultry in Italy between 1999 and 2003. A serological survey of poultry workers was conducted by use of a combination of methods. Evidence of anti-H7 antibodies was observed in 3.8% of serum samples collected from poultry workers during the period in 2003 when LPAI H7N3 virus was ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 11 publications
4
106
0
4
Order By: Relevance
“…They have included serosurveys of bird cullers, open bird market workers, swine workers, duck hunters, meat processing workers, veterinarians and poultry workers, concluding that these populations are indeed at greater risk of infection with zoonotic influenza virus 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…They have included serosurveys of bird cullers, open bird market workers, swine workers, duck hunters, meat processing workers, veterinarians and poultry workers, concluding that these populations are indeed at greater risk of infection with zoonotic influenza virus 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…However, HPAI viruses may emerge by mutation from low pathogenicity AI (LPAI) viruses of the H5 and H7 subtypes circulating in domestic poultry [2,3], and both LPAI and HPAI viruses can infect humans [4][5][6], which stresses the need for the monitoring and control of LPAI viruses in poultry.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 However, several studies indicate that workers have been infected during AI outbreaks in poultry. [27][28][29][30][31][32][33] A serological evaluation of workers exposed during the HPAI H5N1 outbreak in Hong Kong in 1997 found that approximately 3% of government workers involved in the poultry culling operation and 10% of poultry workers were seropositive. 28 During a 2003 outbreak of HPAI H7N7 in the Netherlands, infection was confirmed in 89 people, with conjunctivitis being the predominant symptom reported.…”
Section: Discussionmentioning
confidence: 99%